Studies on Homalomeneae (Araceae) of Borneo XVIII: Homalomena prolixa and H. scutata, two new species of doubtful affinity - Wong, Sin Yeng; Boyce, P.C (BGBM Berlin-Dahlem., 2014)
Two taxonomically novel species of Homalomena (Araceae: Homalomeneae), H. prolixa S. Y. Wong & P. C. Boyce and H. scutata S. Y. Wong & P. C. Boyce, both of doubtful taxonomic affinity, are described from SW Sarawak, and from Brunei and adjacent NE Sarawak, Borneo, respectively. Both occur as lithophytes on forested sandstone bluffs.